Psychometric evaluation of the reliability and validity of the literacy of suicide scale among Chinese nurses - Xie, Zheshu; Lin, Juanjuan; Fan, Ying; Tan, Feirong; Zhou, Yumei; Liu, Xing (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to Sinicize the Literacy of Suicide Scale (LOSS) and to test the reliability and validity of the LOSS with Chinese nurses.MethodsAfter authorization was obtained from the original author, the LOSS was translated into Chinese and translated back into English in accordance with Brislin’s translation principle. Eight experts were invited to evaluate the scale’s content validity, and the Chinese version of the LOSS was obtained. Moreover, the LOSS was used to assess the suicide literacy of 1,000 nurses from Beijing, Hubei, Henan, and Sichuan Provinces in China, and the reliability and validity of the scale were tested.ResultsThe Chinese version of the LOSS contains 26 items covering four dimensions: signs of suicide, risk factors for suicide, the cause/nature of suicide, and the treatment/prevention of suicide. Cronbach’s α coefficient for the LOSS was 0.933, and Cronbach’s α coefficients of the four dimensions were 0.832, 0.893, 0.898, and 0.827. The split-half reliability of the LOSS was 0.818, and the split-half reliabilities of the four dimensions were 0.835, 0.877, 0.890, and 0.819. The test–retest reliability of the LOSS was 0.925, and the test–retest reliabilities of the four dimensions were 0.890, 0.885, 0.892, and 0.904. The item-level content validity index (I-CVI) of the scale was 0.875–1.000, and the scale-level content validity index (S-CVI) was 0.947. Four common factors were extracted via exploratory factor analysis, and the cumulative variance contribution rate was 60.233%. The confirmatory factor analysis results show that the model had a good fit.ConclusionThe Chinese version of the LOSS has good reliability and validity and is a suitable assessment tool for assessing nurses’ suicide literacy in the Chinese cultural context.